Bibliography: Recent Publications in Canadian Labour History - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1998)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]

Bibliography: Recent Publications in Canadian Labour History = Bibliographie : Travaux récents en histoire des classes populaires canadiennes [32, Fall 1993] - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1993)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]

Bibliography: Recent Publications in Canadian Labour History = Bibliographie : Travaux récents en histoire des classes populaires canadiennes (30, Fall 1992) - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1992)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.
Keywords: BIBLIOGRAPHY (Documentation); Labor

Recent Publications in Canadian Labour History = Travaux récents en histoire des classes populaires canadiennes. - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1991)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.

The Canadian Labour Bibliography = La Bibliographique du mouvement ouvrier canadien, 1986-1987 - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1991)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]

The Canadian Labour Bibliography = La Bibliographique du mouvement ouvrier Canadien - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1990)

Recent Publications in Canadian Labour History = Travaux récents en histoire des classes populaires canadiennes - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1995)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University.]

Bibliography: Recent Publications in Canadian Labour History / Bibliographie : Travaux récents en histoire des classes populaires canadiennes - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1997)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]